From temple to tent : from real to virtual world (Exodus 24: 15-- Numbers 10:20) - Hart, Sarah L. (Adelaide : ATF Theology, 2019)
The principle interest of the text on the tabernacle tent, Exodus 24:15-- Numbers 10:28, is Israelite worship--cultic place, the cultic people, and laws for the regulation of cultic life. The method followed is description of the biblical text and collation of the evidence as would a classicist go about classifying an ancient Greek vase. The findings reveal a virtual world of Israelite cult. The transportable tabernacle tent with its courtyard and altar resembles a temple in its complexity. Through words the reader is invited into the atmosphere of the tabernacle tent where all the senses are evoked. The beautifully embellished fore-room of the tent illuminated by the light of the lamp-stand is seen, the waft of the incense smelt, the atmosphere of fear or attraction that emanates from the epicentre of holiness felt. The tabernacle tent is constructed of words, not of stones. It is indestructible and does not succumb to the vagaries of time, as pristine today as it was over 2,500 years ago when it was first created.
From temple to tent
Includes bibliographical references.
Keywords: Bible.O.T. Exodus XXIV, 15-- XL, 38 -- Crirticism, interpretation, etc; Bible.O.T. Leviticus -- Criticism, interpretation, etc; Bible.O.T. Numbers I, 1-- X, 28 -- Criticism, interpretation, etc; Jewish diaspora; Tabernacle; Temple of Jerusalem (Jerusalem)